Gostinho de alegria: a redução da seletividade alimentar de crianças por meio do design emocional - Provenzi, Yasmin (My University, 2019)
Nowadays, feeding is a very recurring issue and this paper will address one of the main problems within this context: food selectivity, that especially affects preschoolers. During this research and from in-depth interviews with mothers and specialists, it was possible observe that this difficulty has changed the routine of both parents, who are unable to feed their own children and, in the same time, children who are not comfortable trying new ones foods. In this sense, we propose to use a design methodology capable of understanding people's needs and desires, in order to find alternatives to alleviate this problem. Ever since, with the support of other specific references for product, brand and service development, the result was the development of a website that prepares specific kits for children with food selectivity and an educational game, downloadable, about food. A visual identity system and kitchen utensils aimed at children were created with the purpose of providing integration between parents and children in the moments dedicated to meals. [resumo fornecido pelo autor]
A alimentação é um assunto bastante recorrente nos dias atuais e este trabalho irá tratar sobre um dos principais problemas dentro desse contexto, a seletividade alimentar, que afeta especialmente crianças em idade pré-escolar. Ao desenvolver pesquisas e fazer entrevistas em profundidade com mães e especialistas, pode-se observar que essa dificuldade altera a rotina tanto dos pais, que se sentem incapazes de alimentar os próprios filhos, quanto das crianças, que não se sentem à vontade para experimentar novos alimentos. Nesse sentido, buscou-se a utilização de uma metodologia de design capaz de compreender as necessidades e desejos das pessoas, a fim de encontrar alternativas para amenizar esse problema. A partir de então, com o suporte de outros autores específicos para desenvolvimento de produto, marca e serviço, obteve-se como resultado o desenvolvimento de um site que prepara kits específicos para crianças que apresentam seletividade alimentar e um jogo educacional sobre alimentação para download. Foram criados, ainda, um sistema de identidade visual e utensílios de cozinha voltados ao público infantil, com o propósito de proporcionar integração entre pais e filhos nos momentos dedicados às refeições. [resumo fornecido pelo autor]
Keywords: Design; Crianças - Nutrição; Alimentos